The Importance of Cultural and Socioeconomic Context in Health Research Design--- Lessons Learnt from a Pilot Study in Pakistan - Sumaira Nasim; Nicola Mary Lowe; Victoria Hall Moran; Stephanie Dillon; Mukhtiar Zaman; Zia Ul-Haq (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: For many health outcomes, there are an array of published methods; however, not all have been validated in the target population. So, it is better to first pilot the selected tools and research strategies, thus can reduce cost, effort and time in a larger project. The objective of this study was to present the significance of the pilot study by using an example of an observational study in a tertiary care hospital in Pakistan.METHODOLOGY: This pilot study was carried out in a tertiary hospital located in Peshawar, Pakistan. The data (Socio-demographics, anthropometric measurements, biochemical tests, blood pressure measurement and diet intake) was collected from the un-paid female caregivers looking after hemodialysis-dependent family members. The caregiver experience was assessed using the Zarit burden interview (ZBI) scale. Pregnant and lactating caregivers were excluded.RESULTS: Data were collected from 20 participants. The decision to participate in the study was based on male family members. Females were reluctant to provide anthropometric measurements and were not aware of monthly income. The majorities were interested in blood pressure measurement and blood tests as offered free of cost. Almost all participants reported positive aspects of caregiving. Thus, ZBI was not found suitable in the selected sample.CONCLUSION: The results of the pilot study highlighted the strengths and limitations of the selected data collection tools. The results of the survey can be useful for the healthcare professionals involved in researching South Asian family caregivers.